An atomic force microscopy study of the growth of a calcite surface as a function of calcium/total carbonate concentration ratio in solution at constant supersaturation - Perdikouri, C.; Putnis, Christine; Kasioptas, A.; Putnis, Andrew (American Chemical Society, 2009)
Calcite growth experiments using atomic force microscopy (AFM) were conducted at two constant values of supersaturation (Qi = 5.248 and £22 = 6.457) while varying the Ca2+to CO32-concentration ratio. The calcite growth rate and the morphology of growth depend on the solution stoichiometry. At a constant degree of supersaturation, the growth rate was highest when the cation/total carbonate anion ratio, r*, was equal to 1 but decreased nonsymmetrically for higher or lower values of r*. The observed dependence of growth, rates on solution stoichiometry can be explained by nonequivalent attachment frequencies of cation and anion at ratios that differ from 1. At the same time, the morphology of the closing etch pits and of the forming nuclei was different when the rate changed, suggesting a change in the crystal growth mechanism. © 2009 American Chemical Society.